Psychopathology following torture experiences: a retrospective record review of victims of torture presenting to the Southern African Centre for Survivors of Torture (SACST) - Raghubir, Latisha (My University, 2015)
Introduction In a constant quest for political power and control incredulously extending from medieval times to present day, the infliction of physical and psychological torture on each other by warring factions is sadly an ongoing reality worldwide. These gross insults on human rights may have a significant impact on the psychological wellbeing of the tortured individuals and result in clinical psychiatric illness. Methods A retrospective record review of all clients visiting the Southern African Centre for Survivors of Torture (SACST) in Johannesburg over a one year period was conducted. Their demographic profiles and torture experiences were analysed using the information available in the centre’s record system. The prevalence of psychiatric illness within this study group was explored. Attempts were made to ascertain differences in trauma experiences endured and psychopathology sustained. The validity of the Self Reporting Questionnaire 8 (SRQ8) rating scale as a screening tool for psychiatric illness was also evaluated. Ethics approval to conduct the study was obtained from the University of the Witwatersrand Human Research Ethics Committee (Medical). IV Results The cases studied were predominantly married, previously employed males less than 40 years old with at least a secondary level of education. All of these cases had experienced some form of torture but their SRQ 8 scores were variable and could not be linked to a specific torture experience or psychiatric diagnosis. Those cases finally assessed by a psychiatrist were all suffering from a psychiatric disorder with a significant 55% diagnosed with a comorbid Major Depressive Disorder (MDD) with Post Traumatic Stress Disorder (PTSD). Only 8% had an isolated PTSD and 24% unipolar depression alone. Conclusion The political conflict occurring in neighbouring Zimbabwe has resulted in large numbers of their nationals fleeing across their borders and seeking refuge in South Africa due to alleged human rights abuses including political torture. Assessment of a small percentage of these individuals in this local study has confirmed the prevalence on MDD, PTSD and combined MDD/ PTSD in this population
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Psychiatry Johannesburg, October 2014
Keywords: Psychopathology; Torture